Assessing the Integration of UN Sustainable Development Goals in the Business Curricula in HEIs: English - Daryl F. Quinco (Research Synergy Foundation, 2026)
The integration of sustainability into higher education is now a global priority, especially in business education. Future professionals are expected to balance economic performance with social responsibility and environmental stewardship. This study examined how sustainability is embedded in the business curriculum of selected higher education institutions in Misamis Occidental and Zamboanga del Norte, Philippines. It also assessed students’ familiarity with sustainability concepts and the United Nations Sustainable Development Goals (UN SDGs), as well as their perceived importance of sustainability integration. A quantitative descriptive design was used. Data were collected from 102 undergraduate business students through a structured questionnaire with Likert-scale items and selected open-ended questions. Results show moderate familiarity with the environmental, social, and economic dimensions of sustainability. The economic area scored lowest despite the business context. Familiarity with the UN SDGs was also limited (M = 2.63). Nearly half of the respondents reported no direct exposure to sustainability-related activities, indicating uneven curricular implementation. Despite these gaps, students strongly agreed that sustainability integration is important (M = 3.92). They associated it with ethical decision-making, critical thinking, professional readiness, and long-term impact. The findings suggest that sustainability is valued but not yet systematically institutionalized across the curriculum. This study contributes by showing that positive student attitudes do not automatically translate into coherent curricular integration. Stronger curriculum mapping, explicit alignment with the SDGs, and expanded experiential learning are needed to achieve comprehensive sustainability education in business programs.